Australian sperm whales from different whaling stocks belong to the same population. Issue 6 (11th January 2021) - Day, Joanna; Power, David; Gales, Rosemary; Bannister, John; Piggott, Maxine P.; Bilgmann, Kerstin; Harcourt, Robert; Beheregaray, Luciano B.; Möller, Luciana M.
Abstract: Understanding the factors driving population structure in marine mammals is needed to evaluate the impacts of previous exploitation, current anthropogenic threats, conservation status, and success of population recovery efforts. Sperm whales are characterized by a worldwide distribution, low genetic diversity, complex patterns of social and genetic structure that differ significantly within and between ocean basins, and a long history of being commercially whaled. In Australia, sperm whales from the (International Whaling Commission assigned) southern hemisphere 'Division 5' stock were very heavily exploited by whaling. The present study assessed the potential effects of whaling on the genetic diversity of sperm whales in Australia and the population genetic structure of these whales within a global context. A combination of historical and contemporary sperm whale samples ( n = 157) were analysed across six regions, from south‐eastern Australia ('Division 6' stock in the Pacific Ocean) to south‐western Australia ('Division 5' stock in the Indian Ocean). Sperm whales sampled from the 'Division 5' and 'Division 6' stocks belong to the same population based on nuclear and mitochondrial DNA (mtDNA) analyses. Four novel sperm whale mtDNA haplotypes were identified in animals from Australian waters. Levels of genetic diversity were low in Australian sperm whales but were similar to those previously reported for populations in the Indian and Pacific Oceans. Given the genetic distinctiveness of sperm whales in Australian waters from other regions in the Pacific and Indian Oceans, and the lack of recovery in population numbers, further scientific studies are needed to increase our understanding of population dynamics and the effectiveness of threat management strategies in this species.